The artificial sweetener neotame negatively regulates the intestinal epithelium directly through T1R3-signaling and indirectly through pathogenic changes to model gut bacteria - Shil, Aparna; Ladeira Faria, Luisa Maria; Walker, Caray Anne; Chichger, Havovi (Frontiers in Nutrition, 2024)
Recent studies have indicated considerable health risks associated with the consumption of artificial sweeteners. Neotame is a relatively new sweetener in the global market however there is still limited data on the impact of neotame on the intestinal epithelium or the commensal microbiota. In the present study, we use a model of the intestinal epithelium (Caco-2) and microbiota (Escherichia coli and Enterococcus faecalis) to investigate how physiologically-relevant exposure of neotame impacts intestinal epithelial cell function, gut bacterial metabolism and pathogenicity, and gut epitheliummicrobiota interactions. Our findings show that neotame causes intestinal epithelial cell apoptosis and death with siRNA knockdown of T1R3 expression significantly attenuating the neotame-induced loss to cell viability. Similarly, neotame exposure results in barrier disruption with enhanced monolayer leak and reduced claudin-3 cell surface expression through a T1R3-dependent pathway. Using the gut bacteria models, E. coli and E. faecalis, neotame significantly increased biofilm formation and metabolites of E. coli, but not E. faecalis, reduced Caco-2 cell viability. In co-culture studies, neotame exposure increased adhesion capacity of E. coli and E. faecalis onto Caco-2 cells and invasion capacity of E. coli. Neotame-induced biofilm formation, E.coli-specific Caco-2 cell death, adhesion and invasion was identified to be meditated through a taste-dependent pathway. In conclusion, our study identifies novel pathogenic effects of neotame on the intestinal epithelium or bacteria alone, and in co-cultures to mimic the gut microbiome. These findings demonstrate the need to better understand food additives common in the global market and the molecular mechanisms underlying potential negative health impacts.